2008
DOI: 10.1186/1756-0500-1-84
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of 1st, 2nd, and 4th year MD students' attitudes toward Complementary Alternative Medicine (CAM)

Abstract: Background: To identify and report the attitudes and beliefs of 1 st , 2 nd , and 4 th year medical students toward complementary alternative medicine (CAM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 9 publications
2
18
0
5
Order By: Relevance
“…Esta proporção, maior que a de oito dos estudos analisados 9,11,[13][14][15][16][17][18] , pode indicar interesse dos sujeitos de pesquisa com relação a este tema, visto que a participação no estudo foi voluntária.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Esta proporção, maior que a de oito dos estudos analisados 9,11,[13][14][15][16][17][18] , pode indicar interesse dos sujeitos de pesquisa com relação a este tema, visto que a participação no estudo foi voluntária.…”
Section: Discussionunclassified
“…Estes dados vão contra o esperado de acordo com a revisão da literatura, que demonstrou declínio das atitudes favoráveis ao longo do curso de Medicina 11,15,21,25 . Este fato tem sido explicado pela tendência dos estudantes dos estágios iniciais a exibir maior idealismo 21 , que seria perdido devido à exposição deles às atitudes negativas com relação às terapias complementares durante o treinamento clínico 12 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…On the other hand, it has been reported that female students in a medical school had significantly more positive attitudes toward CAM than did male students [12][13][14][15] , but several studies have shown no significant difference in gender regarding attitudes toward CAM 16,17) . Therefore, gender difference in the for pharmaceutical students.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown more frequent use of CAM by women than by men for chronic and life-threatening illnesses [8][9][10] . Corbin et al reported that there was a gender difference among US physicians regarding their interest in CAM education and that female physicians were more likely than male physicians to recommend CAM for pa-.On the other hand, it has been reported that female students in a medical school had significantly more positive attitudes toward CAM than did male students [12][13][14][15] , but several studies have shown no significant difference in gender regarding attitudes toward CAM 16,17) . Therefore, gender difference in the…”
mentioning
confidence: 99%